Synthesis of 3-Ethoxy Carbonyl 5-Phenyl-1- p-Tolyl 1,2,4-Triazolo [3,4,-c] 1,2,4-Triazole - SUDHIR KUMAR, P.; NAGOJI, K.E.V.; RAVI KUMAR, B.V.V. (Asian Journal of Chemistry, 2010)
Synthesis of 3-ethoxy carbonyl 5-phenyl-1-p-tolyl 1,2,4-triazolo [3,4,-c] 1,2,4-triazole (5a) by reaction of 5-allylmercapto-5-phenyl 1,2,4-triazole (3) with ethyl chloroglyoxalate p-tolyl hydrazone (4) is described.